Pengaruh Promosi, Kualitas Produk Dan Kualitas Pelayanan Terhadap Minat Pembelian Pada Brand Fashion Visval (Studi Pada Mahasiswa Manajemen UNISMA Angkatan 2020) - Eka Indah Kusmalasari; Muhammad Ridwan Basalamah; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The purpose of this study is to determine the effect of promotion, product quality and service quality on purchase intention at Brand Visval. The research method used is a quantitative method using a questionnaire as a data collection tool. The population in this study were all UNISMA management students class of 2020 who used products from the Visval brand. The number of samples is 100 respondents, using nonprobability sampling technique with purposive sampling. the variable used in this study is Purchase Intention (the dependent variable), while the independent variables are Promotion, Product Quality and Service Quality. This research has met the requirements of validity and reliability. The data analysis used in this study is the classical assumption test, multiple linear regression, hypothesis testing and analysis of the coefficient of determination. The results of this study can be concluded that the variables Promotion, Product Quality and Service Quality affect Purchase Intention. Keywords: Promotion, Product Quality, Service Quality, Purchase Interest.